2020
DOI: 10.4208/csiam-am.2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Review of Entropy Stable Discontinuous Galerkin Methods for Systems of Conservation Laws on Unstructured Simplex Meshes

Abstract: In this paper, we will build a roadmap for the growing literature of high order quadrature-based entropy stable discontinuous Galerkin (DG) methods, trying to elucidate the motivations and emphasize the contributions. Compared to the classic DG method which is only provably stable for the square entropy, these DG methods can be tailored to satisfy an arbitrary given entropy inequality, and do not require exact integration. The methodology is within the summation-by-parts (SBP) paradigm, such that the discrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 51 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…The extension of the DGSEM methods to simplicial grids (see [11] for an overview) could be implemented with a few minor modifications. Based on earlier work [22], the necessary basis function implementations for arbitrary quadrature points are available but need to be integrated into the Dune-Fem and Dune-Fem-DG framework.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extension of the DGSEM methods to simplicial grids (see [11] for an overview) could be implemented with a few minor modifications. Based on earlier work [22], the necessary basis function implementations for arbitrary quadrature points are available but need to be integrated into the Dune-Fem and Dune-Fem-DG framework.…”
Section: Discussionmentioning
confidence: 99%
“…with J E being a smoothness indicator detailed in (11) and TOL a threshold that can be influenced by the user.…”
Section: Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often useful to mimic the same procedure at the discrete level by using summation by parts (SBP) operators, which are constructed specifically to satisfy a discrete analogue of integration by parts. A review of the relevant theory can be found in [16,26,76]. Many classes of numerical methods can be formulated within the SBP framework, including finite difference [75], finite volume [52,53], continuous Galerkin [1,34,35], discontinuous Galerkin [30], and flux reconstruction methods [69].…”
Section: Spatial Semidiscretizationsmentioning
confidence: 99%
“…To mimic this procedure at the semidiscrete level (discrete in space, continuous in time), summation by parts (SBP) operators are used, which provide a discrete analogue of integration by parts. A review of the relevant theory can be found in [28,41,95]. Nowadays, many different schemes have been formulated in the SBP framework, e.g.…”
Section: Introductionmentioning
confidence: 99%